Konsepsi Hukum Mahar Cryptocurrency dalam Perkawinan - Boby Juliansjah Megah Miko (Universitas Batanghari Jambi, 2022)
Islam gives women's rights perfectly without being reduced, this is to protect the honor of women in marriage. Islam also provides women's rights that must be fulfilled by husbands as husbands also have rights that must be fulfilled by wives. Among the rights of the wife is dowry, which is an ownership that is specifically given to women as an expression to appreciate it, and as a symbol to glorify and make her happy. However, the ownership of cryptocurrency as a marriage dowry in marital property is not clear yet and also regarding the transfer of rights to crypto assets because the marriage dowry is how it is implemented according to the provisions of applicable laws and regulations. The problem approach used in this study is a statutory approach, and a conceptual approach. Crypto dowry as property in marriage is included as innate property due to the concept of dowry which is a gift from the prospective groom at the time the marriage contract is held and the transfer of crypto asset rights as a dowry in marriage can be done with a grant deed which is made before the marriage contract in front of a notary who are attended by the grooms. Then the grant deed is given at the time of the marriage contract.